Parasitological and immunological responses of genetically resistant Merino sheep on pastures contaminated with parasitic nematodes - Gray, G.D.; Barger, I.A.; Le Jambre, L.F.; Douch, P.G.C. (International journal for parasitology, 1992)
One hundred and twenty lambs were grazed continuously from weaning until 9 months of age on 12 plots contaminated with larvae of three nematode species ( Haemonchus contortus, Trichostrongylus colubriformis and Ostertagia circumcincta). The lambs were sired by either a genetically resistant ram or susceptible rams (determined by the response of previous progeny to artificial H. contortus infection). Half the resistant and half the susceptible lambs were given strategic anthelmintic treatment and the remainder remained untreated. Faecal egg counts and blood packed cell volume were measured frequently in all animals. One and 5 months after weaning, two lambs from each plot were slaughtered, and worm burdens and larval establishment rates of the three species of nematode were estimated. At the second slaughter, leukotriene levels and larval migration inhibitory (LMI) activity were measured in mucus collected from the small intestine. The dominant species in all faecal samples and the gastrointestinal tract was T. colubriformis. Lambs of the resistant genotype had lower faecal worm egg counts, lower worm burdens and higher levels of resistance to larval establishment. There were no differences in larval migration inhibition (LMI) activity, but resistant lambs had higher levels of the leukotriene LTC 4/D 4/E 4. Further, the resistant genotype, identified on responsiveness to artificial infections with H. contortus, was more resistant to infections of three important species acquired naturally from contaminated pastures. All these genetic differences were maintained while the lambs were subject to strategic anthelmintic treatment.